Cognitive-semantic schemes of indefinite quantification systems in Quechua and Asháninka - Llanto Chávez, Lilia (2014)
This article presents initial important results about a register of non-defined quantifiers in the quechua and ashaninka languages. There are particular cognitive schemas representing the non-defined quantifiers in these languages. They are different, for example, compared with the semantic schemas produced by the Spanish espeakers. The speakers of indigenous languages (Quechua and Ashaninka) relate the non-defined quantity expressions with the notion of quantity units in a holistical way. These quantifiers are related with physical referents because of their own cultural framework which go in the process of their development.